(untitled) (Hoboken, N.J., 2008)
For years, many veterinary treatments for cats were based on research conducted with dogs because it was wrongly assumed that cats were very similar. Recently, there have been giant strides in feline veterinary research. This classic reference is fully updated and revised to reflect these advances and gives you the most up-to-date guidance on cat health and cat care.
Keywords: Cats,Con mèo; Diseases,Bệnh